Regional hyperthermia for soft tissue sarcoma – a survey on current practice, controversies and consensus among 12 European centers - Siyer Roohani; Felix Ehret; Marcus Beck; Danai P. Veltsista; Jacek Nadobny; Sebastian Zschaeck; Sultan Abdel-Rahman; Franziska Eckert; Anne Flörcken; Rolf D. Issels; Stephan Klöck; Robert Krempien; et al. (International Journal of Hyperthermia)
Purpose To analyze the current practice of regional hyperthermia (RHT) for soft tissue sarcoma (STS) at 12 European centers to provide an overview, find consensuses and identify controversies necessary for future guidelines and clinical trials.Methods In this cross-sectional survey study, a 27-item questionnaire assessing clinical subjects and procedural details on RHT for STS was distributed to 12 European cancer centers for RHT.Results We have identified seven controversies and five consensus points. Of 12 centers, 6 offer both, RHT with chemotherapy (CTX) or with radiotherapy (RT). Two centers only offer RHT with CTX and four centers only offer RHT with RT. All 12 centers apply RHT for localized, high-risk STS of the extremities, trunk wall and retroperitoneum. However, eight centers also use RHT in metastatic STS, five in palliative STS, eight for superficial STS and six for low-grade STS. Pretherapeutic imaging for RHT treatment planning is used by 10 centers, 9 centers set 40–43 °C as the intratumoral target temperature, and all centers use skin detectors or probes in body orifices for thermometry.Discussion There is disagreement regarding the integration of RHT in contemporary interdisciplinary care of STS patients. Many clinical controversies exist that require a standardized consensus guideline and innovative study ideas. At the same time, our data has shown that existing guidelines and decades of experience with the technique of RHT have mostly standardized procedural aspects.Conclusions The provided results may serve as a basis for future guidelines and inform future clinical trials for RHT in STS patients.